DECIPHERING THE GENETIC CODES: GENE ACTION AND COMBINING ABILITY IN GOSSYPIUM HIRSUTUM L. AND THEIR IMPACT ON PLANT TRAITS - KHAN , Z; GUL , N; MEHBOOB , A; AMJAD , S; MUNIR , T; HAMMAD , M; SARDAR , H; AKBAR , F; SAQIB , M; MAHMOOD , K (Biological and Clinical Sciences Research Journal, 2023)
Cotton, scientifically known as Gossypium, is a crucial agricultural and economic commodity, widely used for its soft, durable fibers in the textile industry. This study conducted a comprehensive 5x5 full diallel analysis on five cotton genotypes: FH-114, FH-207, CRS-456, MNH-992, and KAHKASHAN. The primary focus was to investigate the combining ability effects and gene action contributions for various plant traits. Key traits examined included plant height, the number of direct and indirect fruit-bearing branches, the first fruiting branch’s position, yield, and related characteristics. Data gathered for these traits underwent thorough statistical analysis. The F-values derived from this statistical evaluation revealed significant variation across all examined parameters in the F1 generations. Results observed from the complete diallel mating design indicate that the collected data for all parameters were enough for Griffing’s approach (1956). Combining ability analysis for all parameters presented the maximum differences for GCA and SCA effects. Less contribution of the GCA variance determines that the traits such as the height of plant, indirect fruit bearing branches, weight of individual boll, seed cotton yield of the individual plant, lint index seed index, percentage of lint, number of bolls on a single plant and first fruiting branch is governed by non-additive type of gene action because the value of GCA/SCA ratio is less than one which indicates that hybrids are more vigorous for all parameter under study. Still, the greater contribution of GCA variance indicates that the traits such as direct fruit bearing branches are largely controlled by dominant gene action because the value of GCA/SCA is greater than one.